CANCER CAREGIVERS’ DISCRIMINATION AND ITS IMPACT TO QUALITY OF LIFE - Duci, Veronika; Ajdini, Juliana; Dhembo, Elona (European Scientific Journal, ESJ, 2014)
Family caregivers can face many challenges in their caregiving role like employment discrimination, making accomodations to work, low average monthly income etc. This is also the case for the cancer caregivers in the albanian context. The aim of this study is to explore the impact that caregiving has in cancer caregiver’s Quality of Life, mediated by the socio – economic status. The participants of this study (N=377) were cancer caregivers for at least one month for an hour/per day. They were contacted at the University Hospital “Nene Tereza” in Tirana, at the Oncology Section. The research instrument consisted in socio – economic questions and the Flanagan Quality of Life Scale (1982). Results indicated that cancer caregivers had low family monthly income and were mostly unenmployed which correlated positively to Quality of Life.